Variation analysis of fruit traits of jujube seedlings and screening of excellent germplasm - JI Yinzhong; CHEN Youfu; YAN Fenfen; WANG Jiurui; LIU Mengjun (Guoshu xuebao)
[Objective] The study aimed to explore the segregation characteristics and genetic variation of fruit traits in jujube (Ziziphus jujuba Mill.) seedlings in order to provide a theoretical basis for jujube seedling selection and cultivar breeding. [Methods] 112 jujube seedling trees of Dongzao and Yuhongas were used as research materials, 37 traits such as fruit maturity, high yield, appearance quality, sensory quality, nutritional quality and resistance were identified for investigation. The genetic variation of fruit traits were analyzed, and the gray correlation analysis was used to screen excellent jujube seedlings. [Results] The 17 fruit descriptive traits of the two jujube seedling populations segregated a total of 57 types, exhibiting rich variation and a wide range of segregation phenomena. The fruit shape of Dongzao seedling population consisted of 7 types, exhibiting the widest range of segregation, with the flat-round shape resembling that of Dongzao accounting for 40.79%. The fruit shape of Yuhong seedling population exhibited 6 types, with the elongated shape being the most common, comprising 38.89%, while the conical shape consistent with the Yuhong accounted for 27.78%. Over 44.74% fruits of the two jujube seedling populations was sweet, consistent with Dongzao and Yuhong. Among them, the fruits with thin fruit skin of the Dongzao seedling population accounted for 39.47%, and those with crispy fruit flesh accounted for 57.89%. The variation in single fruit weight was quite significant, and the fruit weight of the Dongzao population ranged from 2.11 g to 30.25 g, indicating a broad degree of segregation, nd the fruit weight of 34.21% of the population exceeded the weight of the female parent. The maximum single fruit weight and fruit diameter were 19.34 g and 11.48 m, respectively, higher than those of Dongzao. The average single fruit weight and fruit diameter of Dongzao were both higher than those of the Yuhong population, indicating that Dongzao has a greater potential for selecting large fruit. The coefficient of variation for intrinsic quality traits ranged from 7.51% to 64.72%. Among these, the Dongzao and Yuhong seedling populations showed a rate of exceeding the maternal parent for titratable acid content, vitamin C content, and flavonoid content of over 57.89%. The variation in soluble solids content was considerable, with the Dongzao population exhibiting a rate of exceeding the maternal parent of up to 51.32%, and the average value was also higher than that of the maternal parent. This indicated that the Dongzao jujube seedlings exhibited a phenomenon of exceeding the maternal parent in soluble solids, which was beneficial for selecting high-soluble solid resources. The maximum values of soluble sugar content in the Dongzao and Yuhong populations were both above 31.73%, which was advantageous for selecting high-sugar resources. The coefficient of variation for titratable acid content in the two jujube populations was over 47.86%, indicating a wide variation in titratable acid content. The rate of exceeding the maternal parent for titratable acid in the two offspring reached 66.67%, with the average also higher than that of the maternal parent, facilitating the selection of high-acid resources. The coefficient of variation for vitamin C content in the two offspring was 23.50%, with the highest variation range of 754.27 mg·100 g-1. The ripening stage of Dongzao seedling population ranged from early September to late October. More than 56.58% of the individuals in the seedling populations exhibited good crack resistance and fruiting ability. Based on genetic distribution characteristics, the fruit length and diameter of the Dongzao and Yuhong seedlings both were conformed to a normal distribution. However, the Dongzao population showed a significantly higher occurrence of large single fruit weights compared with the Yuhong population, indicating that the Dongzao offspring possessed greater potential for developing large fruit germplasm. The soluble sugar content and total phenolic content of the Dongzao and Yuhong population were also conformed to a normal distribution. The normal fitting curve for the soluble solids of the Yuhong offspring was longer on the lower side, with a greater concentration of data points on the upper side, indicating that there were more population with higher values of soluble solids. Both the Dongzao and Yuhong population exhibited points outside the upper side of the normal curve for titratable acid, suggesting the presence of high-acid resources in both offsprings. Notably, the normal fitting curve for vitamin C in the Dongzao population was longer on the upper side and had more data points, indicating that the Dongzao population were likely to produce high vitamin C resources. [Conclusion] A total of 13 excellent fresh jujube germplasm resources with a comprehensive taste were selected through gray correlation analysis, along with 5 outstanding germplasm resources for dried jujude processing with a drying rate of ≥42.00%. Additionally, 12 specific germplasm resources were identified, including 4 resources with soluble sugar content ≥30.00%, 3 resources with titratable acid content ≥1.40%, and 5 resources with vitamin C content ≥591.00 mg·100 g-1.